Pengaruh Motivasi da Kepuasan Kerja terhadap Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kota Palangka Raya - Asie Asie; Hairudinor Hairudinor; M. Noor Rasyidi (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
This study aimed to examine the effect of motivation (X1) and Job Satisfaction (X2) the Employee Performance (Y) On Perusahaan Daerah Air Minum (PDAM) Kota Palangka Raya.  Samples taken as many as 67 employees elected saturated sampling technique. Collecting data using questionnaires, while data analysis using SPSS version 21.00. The results of this study prove the motivation (X1) partially not significant effect on employee performance (Y) with 8.4% and the major influence job satisfaction (X2) partially significant effect on employee performance (Y) with large effect 90,3% , while simultaneously motivation (X1) and Job Satisfaction (X1) effect on employee performance (Y) with large effect 69,2% and 30.8% influenced by other variables , Implementation of this research that in order to improve the performance of employees need to pay attention to Motivation and Job Satisfaction.   Keywords: Motivation, Job Satisfaction, Employee Performance